2021
DOI: 10.1097/md.0000000000026485
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and influencing factors of fever in postoperative patients undergoing percutaneous nephrolithotomy

Abstract: Percutaneous nephrolithotomy (PCNL) is commonly used for the treatment of upper urinary calculi in clinical setting, and fever is a common complication after PCNL. It is necessary to evaluate the risk factors of fever in patients undergoing PCNL, to provide insights into the management of PCNL. Patients who underwent PCNL in our hospital from January 2018 to August 2020 were included. The clinical data of postoperative fever and no fever patients were collected and assessed. Logistic regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Postoperative fever is common in patients undergoing cytoreductive surgery. A postoperative body temperature rise (< 38.3°C) does not require special treatment [29]. In this study, we found that patients with visceral obesity were more likely to have postoperative fever and a postoperative body temperature ≥ 38.3°C.…”
Section: Discussionmentioning
confidence: 57%
“…Postoperative fever is common in patients undergoing cytoreductive surgery. A postoperative body temperature rise (< 38.3°C) does not require special treatment [29]. In this study, we found that patients with visceral obesity were more likely to have postoperative fever and a postoperative body temperature ≥ 38.3°C.…”
Section: Discussionmentioning
confidence: 57%
“…Researchers have reported that staghorn stones usually cause upper urinary tract obstruction and UTI [ 34 , 35 ]. When the urinary tract is obstructed, the various strains of bacteria on the surface of the stones are colonized and grow in large numbers in the renal pelvis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%